ANALISIS SWOT SEBAGAI PENENTU STRATEGI BERSAING PERUSAHAAN - Samudra, Hengki; Ariffianti, Indah; Sapitri, Ria Rosmalasari (Valid Jurnal Ilmiah, 2017)
This research entitled the "SWOT Analysis As Determinants of Corporate Competitive Strategy (Studies in Carissa Salon in Mataram City)". This research aims to determine the position of Carissa Salon business based on SWOT analysis as well as to determine the right competitive strategy undertaken by Carissa Salon. This research is descriptive research. Methods of data collection in this research using a sample survey with a sampling technique using Snowball Sampling. The data collection techniques used in this research is by interview and documentation. While the data collection tool is questionnaires. Based on the results of SWOT analysis is performed using tables EFAS and IFAS known that the company is in a Weakness-Opportunities (WO) position, this can be seen from the total scores for weakness by 1.72 greater than the total score of the power of 1.56 on the IFAS table, and based of EFAS table shows that the total score for opportunities by 1.64 greater than the total threat score of 1.08. As for the right competitive strategy undertaken by Carissa Salon based of SWOT analysis is a strategy to improve itself which is a strategy to minimize the weaknesses by making use of existing opportunities